Jogos no processo de ensino-aprendizagem em probabilidade - Silva, Fabrício Menezes Netto da (2013)
This work has as a goal to stimulate good pedagogical practices aiming the best learning from students in Probability, through daily applications and/or games. Besides, it has as highlight a teaching sequence proposal inspired by TV Show ( O último passageiro) to analyze this subject, which it was developed through stimulations of game, debates, probability calculation and construction of graphics with students of 2nd and 3rd grade in High School at a public school Escola Estadual Professor Roque Ielo , Caconde-SP, aiming to transform theoretical approach of this knowledge into a constructivist approach stimulating the student to be the protagonist.